Transcranial Direct-Current Stimulation as an Adjunct to Verb Network Strengthening Treatment in Post-stroke Chronic Aphasia: A Double-Blinded Randomized Feasibility Study - Matar, Shereen J.; Newton, Caroline; Sorinola, Isaac O.; Pavlou, Marousa (Frontiers in Neurology, 2022)
Background: Difficulties in discourse production are common in post-stroke chronic aphasia. Previous studies have found that speech and language therapy combined with transcranial direct-current stimulation (tDCS) may improve language skills like naming and enhance aphasia treatment outcomes. However, very few studies have investigated the effect of tDCS when combined with interventions for improving higher level language skills such as the Verb Network Strengthening Treatment (VNeST). Aims: This study aimed to determine the feasibility of anodal tDCS as an adjunct to VNeST to improve discourse production in post-stroke chronic aphasia. Methods: Six people with post-stroke chronic aphasia took part in this double-blinded randomized feasibility study. Participants were randomly allocated to either the experimental group receiving a six-week block of once weekly VNeST sessions combined with active tDCS over the left inferior frontal gyrus (LIFG) or a control group that received VNeST with sham stimulation. Feasibility outcomes included screening, eligibility, retention and completion rates and adverse events. Preliminary response to intervention was also examined using discourse production, functional communication, quality of life, psychological state and cognition outcomes. Results: Overall 19 individuals were screened and ten met the inclusion criteria. Six individuals provided consent and participated in the study giving a consent rate of 60%. Participant retention and completion rates were 100% and no adverse effects were reported. Exploratory analyses revealed promising changes (i.e., estimated large effect size) in discourse production measures across discourse language tasks and functional communication for the active tDCS group. Conclusions: Our results support the feasibility of tDCS as an adjunct to VNeST. Preliminary findings provide motivation for future large-scale studies to better understand the potential of tDCS as a safe and economical tool for enhancing rehabilitation in chronic aphasia.